(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
ABSTRACT: This article aims to bring discussion about the practical effectiveness of the Constitutional Regime of Socially Protected Employment, within the very conception of social constitutionalism, which extols the promotional rule linked to the idea of ​​the balanced work environment, as a subjective right of the worker, constitutional ethos, from the perception of a new paradigm introduced with the rule of art. 7, item XXII, of CF / 88, recognizing the effective protection of the artificial environment referred to in art. 200, item VIII, of CF / 88, represented by the environmental working conditions. In this direction, there would be a break with the prescription of mere conformity of the programmatic norm of art. 158, item IX, of CF / 67 and EC No. 1/69, which formally deals with matters related to Occupational Health and Safety. And in order to effectively break with the outdated notion of the monetization of risk, we would have to follow the path that acknowledges its effectiveness in the infraconstitutional plan by the intermediate categorization of the employee’s presumption of guilt, situated between objective and subjective responsibility, based on cool in art. 21-A, of Law No. 8.213 / 91, so that after the Labor Reform (Law No. 13.467 / 17), with its deepening via the introduction of concepts of economic freedom (MP No. 881/19), we do not escape the debate of the propositions that meet the principle of social non-regression, without overflowing with the limits of the fundamental pillar linked to the principle of legality inscribed in art. 5, item II, of the CF, because we are witnessing the recovery of its prestige, in the face of overcoming the contemporary identification of the “crisis of legality”, who goes beyond the doctrinal propositions of the normative force extraction from the Constitution.